2012
DOI: 10.1159/000339638
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Centrifugation Supernatant Fluid from Pancreaticobiliary Duct Samples Can Improve Cancer Detection

Abstract: Objective: We aimed to supplement microscopic examination of biliary cytobrush specimens to improve sensitivity by mutational profiling of: (1) selected cells microdissected from cytology slides and (2) corresponding cell-free DNA in residual supernatant fluid. Study Design: From 43 patients with brushings of bile or pancreatic duct strictures, DNA was extracted from microdissected cells and 1–2 ml of cytocentrifugation supernatant fluid. Mutational analysis targeted 17 genomic sites associated with pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…Notwithstanding, available data on cytology specimens have consistently demonstrated that microdissected stained cytology cells are especially suitable for mutational analysis and applicable to common cytology practice. 17,18,20,23,43 Furthermore, as most of the commonly used fixatives in cytology are alcohol based, and are not expected to induce significant DNA degradation, it would be reasonable to expect favorable results with these other methods of sample preparation of the supernatant fluid as well.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notwithstanding, available data on cytology specimens have consistently demonstrated that microdissected stained cytology cells are especially suitable for mutational analysis and applicable to common cytology practice. 17,18,20,23,43 Furthermore, as most of the commonly used fixatives in cytology are alcohol based, and are not expected to induce significant DNA degradation, it would be reasonable to expect favorable results with these other methods of sample preparation of the supernatant fluid as well.…”
Section: Discussionmentioning
confidence: 99%
“…A panel of 16 microsatellite markers was used for this purpose. These markers targeted common sites for tumor-suppressor genes associated with pancreaticobiliary cancers and have previously undergone analytic and clinical validation for pancreaticobiliary disease as reported in prior studies, [16][17][18][19][20][21][22][23] and present at the following chromosomal locations: 1p (CMM1, Lmyc), 3p (VHL, OGG1), 5q (MCC, APC), 9p (CDKN2A, CDKN2B), 10q (PTEN, MXI1), 17p (TP53), 17q (NME1, RNF43), 21q, 22q (NF2) using quantitative fluorescent PCR/capillary electrophoresis.…”
Section: Molecular Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have also shown that microdissection-based mutational profiling of DNA can be clinically useful in diagnosing these malignancies [10-15]. Such molecular analysis is especially significant when morphologic methods are uncertain or not obtainable [18-22]. Like cytology, the use of mutational profiling has traditionally required cellular material that shows morphological signs of disease in order to extract DNA from microdissected areas of relevant cells.…”
Section: Introductionmentioning
confidence: 99%